2011
DOI: 10.1128/aac.00365-11
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Ex Vivo Antimalarial Activity of Artesunate-Azithromycin in Healthy Volunteers

Abstract: In 18 male healthy subjects, artesunate (200 mg)-azithromycin (1,500 mg) daily for 3 days was found to be well tolerated, with only mild gastrointestinal disturbances reported. The pharmacokinetic properties of artesunate-azithromycin given in combination are comparable to those of the drugs given alone. Artesunate and its major active metabolite, dihydroartemisinin, are responsible for most of the ex vivo antimalarial activity, with a delayed contribution by azithromycin.Artemisinin-based combination therapie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
2
5
1
Order By: Relevance
“…The PK properties of AS, DHA, AQ, and DAQ with and without MB are summarized in Table 1. Overall, the PK properties of AS, DHA, AQ, and DAQ obtained in this study are in broad agreement with those obtained in other studies in healthy volunteers given either AS or AQ alone or in combination with a longer-acting antimalarial drug (27)(28)(29)(30).…”
Section: Resultssupporting
confidence: 90%
“…The PK properties of AS, DHA, AQ, and DAQ with and without MB are summarized in Table 1. Overall, the PK properties of AS, DHA, AQ, and DAQ obtained in this study are in broad agreement with those obtained in other studies in healthy volunteers given either AS or AQ alone or in combination with a longer-acting antimalarial drug (27)(28)(29)(30).…”
Section: Resultssupporting
confidence: 90%
“…The gastrointestinal disturbances were probably azithromycin related as these adverse events were also experienced in healthy Vietnamese volunteers administered the same 3-day ASAZ regimen. 19 The high efficacy and good tolerability of ASAZ reported in the present study further supports earlier studies in Bangladesh 20 and Thailand 21 that showed a 3-day course of azithromycin (30 mg/kg/day)-artesunate (4 mg/kg/day) to be effective (PCR-corrected cure rate > 92%) in curing uncomplicated P. falciparum malaria in adults and children. However, a lower dosage of azithromycin (20 mg/kg) coadministered with artesunate (4 mg/kg) given daily for 3 days in Tanzania 22 and Thailand 21 was less efficacious (PCR-corrected cure rate < 89%), emphasizing the importance of adequate azithromycin dosing.…”
supporting
confidence: 90%
“…The azithromycin dose of 25 mg/kg/day selected in the present study was considered the maximum acceptable dose based on our previous study in healthy Vietnamese volunteers. 19 Prolongation of parasite clearance times (> 72 hours) reported in studies from western Cambodia 23 and south Vietnam 24 with artesunate alone was not evident in the present study, with no patients having parasites present on day 3 after starting treatment, suggesting that the parasite populations were susceptible to artesunate at the time of the study. This was further confirmed with a lack of polymorphism in the PfKelch 13 gene of falciparum parasites sampled from the patients.…”
contrasting
confidence: 65%
“…The ED 50 of artesunate in inhibiting proliferation in multiple NPC cell lines is 16–22 μ m ( Figure ). In the treatment of mild–moderate falciparum malaria, patients receive a single dose of up to 200 mg oral artesunate and serum concentrations of artesunate are less than 10 μ m . However, for severe malaria, intravenous artesunate is recommended in adults .…”
Section: Discussionmentioning
confidence: 99%